The effect of intensive tempo training in development of speed endurance, some physiological indicators, and 800-meter performance in 20 years runners - Ali Abdulameer Hussein, Maytham Fakhri Al-Hammadi, Abbas Khaleel Mohammed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
It is clear in sports training what the training process has had on the physical and physiological condition of the whole body parts and the effectiveness of this training in the occurrence of physical and physiological changes that give a positive result in the performance of the 800-meter competition. The researchers noticed that there is a decrease in speed endurance and a small percentage of the occurrence of insufficient physiological adaptations that occur inside the body, so they decided to set up of intensive tempo exercises in terms of accelerating recovery during the level of physical achievement in the sessions, where the positive effect in achievement in appropriate training requirements for this kind of competition to build their physical potential and prepare the body to adaptation. The research aims to set up intensive tempo exercises and to identify it's effect in development of speed endurance and some physiological indicators and 800-meter performance runners under 20 years. The researchers used the experimental method by pre and post tests for the experimental and control groups, and the research community was the players of the 800-meter in Babel Governorate's clubs for the sport season 2020, (N=16) players chosen as research sample, by a comprehensive inventory method, and the sample was divided into two groups (8) Players for each group. Intensive tempo training applied to the experimental group for eight weeks, with three sessions per a week, and they used the SPSS to process data and obtain results. Physiological indicators and 800 meters performance.